A Rare Case of Large Left Lateral Wall Vaginal Myoma - Shrestha, A.; Mudbari, J.; Tamrakar, S. R.; Pradhan, N.; Makaju, R.; Karki, S. (Kathmandu University Medical Journal, 2021)
Vaginal leiomyomas are rare, they are uncommon benign tumor with variable clinical presentation. They usually present as a mass per vaginum or dyspareunia or pressure symptoms on the neighbouring structures. We present a case of 47 years lady with mass per vaginum and difficulty in walking and chronic pelvic pain. Her clinical findings suggested a large mass in the left vaginal wall, the mass was approximately 12 x 10 cm in size hindering the visualization of the cervix. Her ultrasonography showed bulky uterus with mass occupying the cervix. This finding was not correlating with the clinical findings. Magnetic resonance imaging (MRI) was done and it was reported as mass lesion in pelvis separate from the cervix abutting the rectum posteriorly. Ultrasonography (USG) guided biopsy was done which was reported as Leiomyoma. She underwent vaginal myomectomy and was confirmed in histopathology as Leiomyoma. A leiomyoma is a smooth muscle tumor that arises from the muscular part of the uterus and rarely seen in the vaginal wall.